Pemanfaatan Urin Sapi sebagai Bahan Baku Pupuk Organik Cair (Studi Eksperimen Penambahan Aktifator Air Kelapa dan Gula Merah tahun 2017) - Nurika Octa; Rachmaniyah .; Imam Thohari (GEMA LINGKUNGAN KESEHATAN, 2018)
" Beef is one of waste waste from human activities. Cow's urine must be well managed in order to reduce environmental pollution. Management of bovine urine by means of turning it into a fertilizer in Add Activator coconut milk, brown sugar and EM4 can reduce environmental pollution and beneficial to the plant. The purpose of this research was to analyze the cow's urine as a liquid organic fertilizer raw materials This type of research are True Experiment, with the design of the Posttest Only Control Group Design. Research methods to measure the levels of Nitrogen, phosphorus and Potassium in the treatment and control groups with a dose of a comparison of the coconut milk and brown sugar 240:16, 160:8 and 200:12. The location of the research carried out in the village of Tugu sub-district of Mantup Lamongan. Data is processed using tabulations further described with based on regulation of the Minister of agriculture no. 70/Permentan/SR 140/10/2011. Test results measuring the levels of the most highest value NPK averaged ratanya in the treatment of 1 with doses of a comparison 240:16. For pH values all liquid fertilizer meet the standard is 5 – 6. After applied on plants that grow quickly in plants that give fertilizer with a dose of 240:16. The addition of the EM4, Activator coconut water and brown sugar can change the cow urine into fertilizer Liquid Nitrogen and potassium levels qualify yet for Phosphorus levels have not been qualified. Need to research more about the effective dose in the manufacture of liquid organic fertilizer that meets the terms of the regulation of the Minister of agriculture no. 70/Permentan/SR 140/10/2011 About Biological Fertilizers, organic fertilizers and Pembenah Soil.Keywords : Cow urine, Activator coconut juice, brown sugar and EM4